2017
DOI: 10.1111/ppl.12584
|View full text |Cite
|
Sign up to set email alerts
|

A bell pepper cultivar tolerant to chilling enhanced nitrogen allocation and stress‐related metabolite accumulation in the roots in response to low root‐zone temperature

Abstract: Two bell pepper (Capsicum annuum) cultivars, differing in their response to chilling, were exposed to three levels of root-zone temperatures. Gas exchange, shoot and root phenology, and the pattern of change of the central metabolites and secondary metabolites caffeate and benzoate in the leaves and roots were profiled. Low root-zone temperature significantly inhibited gaseous exchange, with a greater effect on the sensitive commercial pepper hybrid (Canon) than on the new hybrid bred to enhance abiotic stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 61 publications
0
16
0
1
Order By: Relevance
“…Various genes and metabolic pathways have been identified that function in enhancing cold tolerance. Well-known stress tolerance mechanisms including damage to membranes, GABA accumulation and its signaling pathways leading to osmotic adjustment, and other mechanisms associated with various secondary messengers, GABA also leads to transcriptional and post-transcriptional regulation [5, 7, 8]. Numerous genes encoding transcription factors and other metabolites related to cold stress have been reported and used for genetic engineering of plants with enhanced cold tolerance [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Various genes and metabolic pathways have been identified that function in enhancing cold tolerance. Well-known stress tolerance mechanisms including damage to membranes, GABA accumulation and its signaling pathways leading to osmotic adjustment, and other mechanisms associated with various secondary messengers, GABA also leads to transcriptional and post-transcriptional regulation [5, 7, 8]. Numerous genes encoding transcription factors and other metabolites related to cold stress have been reported and used for genetic engineering of plants with enhanced cold tolerance [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of aeroponic systems is their easy-to-use method of monitoring plant nutrition, pH, and electrical conductivity (EC; Tafesse, 2014). This type of system also supports continuous measuring of plant shoots and roots in both non-destructive and destructive methods for analytical analysis in the laboratory (Aidoo et al, 2017). Aeroponic and hydroponic systems are both soilless plant cultures.…”
Section: Introductionmentioning
confidence: 71%
“…Aeroponics is a plant culture technique employed for the growth of plant where the roots are either continuously or periodically misted with a nutrient solution; it may be regarded as a variant of hydroponics where plant roots are constantly cultivated in a nutrient solution (Rubanenko & Hilitsky, 2011). Aeroponics has long been used as a research tool in root physiology (Barak et al, 1996) and is recommended as a technique for steady-state control of nutrients, gas exchanges, root temperature, and moisture (Aidoo et al, 2017;Zobel et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…The alteration of element allocation patterns was always associated with various external surrounding factors, such as temperature [59]. Aidoo et al [60] subjected two cultivars of pepper to a low root zone temperature and found that more nitrogen was allocated to roots to ensure the survival of the whole plant; however, carbon allocation was not affected by low root temperature. In line with Aidoo et al [60], our results in Exp-2 showed that nitrogen tended to accumulate in the roots, while other elements were unaffected.…”
Section: Discussionmentioning
confidence: 99%